Poverty, International Migration and Asylum 2005
DOI: 10.1057/9780230522534_10
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Gains from the Elimination of Global Restrictions on Labour Mobility

Abstract: We compute the world-wide efficiency gains from the elimination of global restrictions on labour mobility using a multiregional CGE model. A distinctive feature of our analysis is the introduction of a segmented labour market, as two types of labour are considered: skilled and unskilled. According to our results, when labour is a homogeneous factor, the elimination of global restrictions on labour mobility generates world-wide efficiency gains that could be of considerable magnitude. When the labour market is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Interestingly, Winters () or Walmsley and Winters () simulated the effect of an exogenous increase in developed countries' immigration quotas on both high‐skilled and low‐skilled migrants equivalent to 3 percent of the labor force (i.e., 0.45 percent of the world labor force). Using a global CGE model with two skill levels, they predicted a $150 billion increase in the world GDP (+0.6 percent), that is, a semi‐elasticity of the world GDP to the share of migrants of 1.33, in line with Iregui () . These optimistic studies suggest that migration barriers leave “trillion dollar bills on the sidewalk” (Pritchett, ; Clemens, ) and see efficiency as a decisive argument for a liberalization of cross‐border migration.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, Winters () or Walmsley and Winters () simulated the effect of an exogenous increase in developed countries' immigration quotas on both high‐skilled and low‐skilled migrants equivalent to 3 percent of the labor force (i.e., 0.45 percent of the world labor force). Using a global CGE model with two skill levels, they predicted a $150 billion increase in the world GDP (+0.6 percent), that is, a semi‐elasticity of the world GDP to the share of migrants of 1.33, in line with Iregui () . These optimistic studies suggest that migration barriers leave “trillion dollar bills on the sidewalk” (Pritchett, ; Clemens, ) and see efficiency as a decisive argument for a liberalization of cross‐border migration.…”
Section: Introductionmentioning
confidence: 98%
“…Less optimistic results are obtained when foreign workers are assumed to be less productive than natives . Iregui () is the only study accounting for differences in workers' educational attainment (i.e., a low‐skilled Mexican migrating to the US is as productive as a low‐skilled US worker, but less than the average American). Under the same set of hypotheses, she finds that relocating people to equalize wages increases the world GDP by 67.0 percent.…”
Section: Introductionmentioning
confidence: 99%
“…That is, a more efficient spatial allocation of labor could raise global output by 50-150%. Decades passed before a series of follow-up studies confirmed the broad magnitude of the Hamilton and Whalley results with more refined macro models (Moses andLetnes 2004, 2005;Iregui 2005;Walmsley and Winters 2005;Klein andVentura 2007, 2009;van der Mensbrugghe and Roland-Holst 2009;surveyed in Clemens 2011). The mag-nitude of these estimates has been corroborated in a series of recent studies (Benhabib and Jovanovic 2012;Kennan 2013;di Giovanni et al 2015;Bradford 2015).…”
Section: Macro Evidencementioning
confidence: 90%
“…Using this approach Iregui (2005) finds that full liberalisation would increase world GDP by between 15 and 67 percent. Of particular interest is the study by Winters et al (2003) who use a model (GTAP) similar to that used to evaluate the gains from liberalising trade.…”
mentioning
confidence: 99%